Analisis Pendapatan Pengrajin Perhiasan di Desa Celuk (Studi Perbandingan Pengrajin Perak Dan Pengrajin Alpaka) - Paramitha Udiana, Ni Wayan Pradnya; Sudiana, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana; vol.6.No. 8. Agustus 2017(pp.1395-1627), 2017)
Celuk becoming known as an area of silver production since 1976. The silver is one part of the art has long been grown in Bali, because it is expensive and the high price of silver is not all people can afford to buy crafts and silver jewelry, so that people many which uses the alternative of buying jewelry that resembles the silver craft called the alpaca craft.  The purposes of this study are to analyze the revenue comparison alpaca silver artisans and craftsmen and to analyze the differences in the production of alpaca silver artisans and craftsmen in Celuk. Based on the results of the study concluded craftsmen’s revenue alpaca is higher than the income of a silversmith. for alpaca jewelry have the price is much cheaper with form and appearance similar to silver jewelry and alpaca jewelry production yield significantly higher than silver jewelry. In production of and the alpaca jewelry is faster than silver jewelry in addition to more competitive prices.
Keywords: Pendapatan; Kerajinan; Hasil Produksi